2017
DOI: 10.4111/icu.2017.58.4.247
|View full text |Cite
|
Sign up to set email alerts
|

How do we diagnose detrusor underactivity? Comparison of diagnostic criteria based on an urodynamic measure

Abstract: PurposeTo compare several contemporary urodynamic criteria for diagnosing detrusor underactivity (DU) and estimate how well they coincide with each other.Materials and MethodsFrom our prospective urodynamic database we identified nonneurogenic lower urinary tract symptoms (LUTS) patients older than 60 years between 2003 and 2014. Patients were reclassified based on four and three contemporary criteria for DU among men and women. Each criterion was compared with the others using the McNemar test.ResultsUrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 12 publications
2
28
0
1
Order By: Relevance
“…22 Medical treatment has been given to the majority of the patients, which might be reflected with missed diagnosis due to the long duration of the prevalent problem and overlap of DU characteristics with other common symptoms such as bladder overactivity, urinary tract infections, and BOO. 23,24 The findings of the current study are supported by the findings of Rademakers et al, 25 who reported a prevalent increase of hesitancy, weak stream, and incomplete bladder emptying in women with DU as compared to men.…”
Section: Discussionsupporting
confidence: 90%
“…22 Medical treatment has been given to the majority of the patients, which might be reflected with missed diagnosis due to the long duration of the prevalent problem and overlap of DU characteristics with other common symptoms such as bladder overactivity, urinary tract infections, and BOO. 23,24 The findings of the current study are supported by the findings of Rademakers et al, 25 who reported a prevalent increase of hesitancy, weak stream, and incomplete bladder emptying in women with DU as compared to men.…”
Section: Discussionsupporting
confidence: 90%
“…The only definitive finding that is confirmed is the presence of an acontractile detrusor muscle, where there is no detrusor pressure recorded during voiding and the patient will void by straining only [1]. Other parameters that were discussed to assess such patients included: P det Q max <30 cmH 2 O, Q max <10 mL/s, and a bladder voiding efficiency (which is voided volume divided by voided volume plus PVR and <90% is suggestive of detrusor underactivity), reduced maximum cystometric capacity, and impaired compliance [47,48]. Therefore, UDS is important in such patients.…”
Section: Detrusor Underactivitymentioning
confidence: 99%
“…In humans, a correct diagnosis of DU is only possible by pressure flow studies that require the simultaneous measurement of detrusor pressure and urine flow . However, a recent study showed a good correlation between pressure flow studies and BVE in women . Moreover, a BVE <60% is commonly used to define DU .…”
Section: Discussionmentioning
confidence: 99%
“…16 However, a recent study showed a good correlation between pressure flow studies and BVE in women. 17 Moreover, a BVE <60% is commonly used to define DU. 18 Therefore, we believe that the BVE of 48% in the aged female rats used in this study is a robust indicator of DU.…”
Section: Discussionmentioning
confidence: 99%